Community Empowerment and Environmental Management through Eco Enzyme Production Training in Kismoyoso Village, Boyolali – Central Java - Agung Hidayat; Ahmad Miftahul ‘Ulum; Alfika Rizka Hapsari; Bilqis Maulida Karimah; Hasna Afifah Janu Ismawati; Herlambang Pangestu; Mutiara Azzahra; Puji Dewi Astuti; Riani Lestari; Rivan Andriawan; Yuta Watanabe (Prospect Publishing, 2023)
The National Waste Management Information System data stated that in 2022, households ranked first as waste and garbage producers with a percentage reaching 43.3%. The issue of household waste management also occurs in Kismoyoso Village. Therefore, community engagement activities through KKN UNS Village Development include conducting socialization and workshops on household waste management through eco enzyme production. The objective of this activity is to raise awareness and encourage the residents of Kismoyoso Village to utilize household waste as something of value and economic worth. The production of eco enzymes is prepared using Dr. Rosukon's method, which involves mixing sugar (palm sugar/white sugar/molasses) with household waste, specifically organic waste, and water in a ratio of 1:3:10. The eco enzyme solution is then left to undergo a 90-day fermentation process.